Glioma Migration Through the Corpus Callosum and the Brainstem Detected by Diffusion and Magnetic Resonance Imaging: Initial Findings - Sharifi, Guive; Pajavand, Amir Mohammad; Nateghinia, Saeedeh; Meybodi, Tohid Emami; Hasooni, Hossein (Frontiers in Human Neuroscience, 2020)
Purpose: The glioma cell infiltration is known as the significant challenge for surgery or localised chemo- and radiation therapy, which the glioma tumour cells spread in long distances from the primarily located structure using white matter or blood vessels. Following the World Health Organization (WHO), glioma grading system ranges from stages I-IV which the lower-grade gliomas deliberated as benign tumours, and clearly, higher grade gliomas are considered the most malignant. Materials and Methods: Based on these data, we gathered MRI and DTI data of 7 patients with right precentral gyrus located tumours and six age and sex-matched healthy subjects for analysing. Tract Based Spatial Statistics (TBSS) done for evaluating whole-brain white matter implication due to the probable tumour infiltration. Also, along tract statistics used in order to trace the implicated WM tracts. Finally, for cortical evaluation due to the probable tumour cell migration, Voxel-Based Morphometry (VBM) was utilised, which allowed us to do whole-brain cortical estimation. Results: TBSS results revealed significantly higher fractional anisotropy (FA) and lower mean diffusivity (MD) of the left side superior corona radiata. Also, higher fractional anisotropy observed in the right corticostriatal tract. Along tract statistics, was also done on the corpus callosum (CC) which is anatomically known as a hub between hemispheres. The body of the CC, which is in connection with the superior corona radiata anatomically showed significant higher FA values relative to healthy subjects, which are in line with the TBSS results. Consistent with these results, whole brain grey matter changes analyzed via VBM, which showed significant hypertrophy of both sides of the brainstem. Conclusion: Future investigations, focusing on the genetic basis of the glioma patients in line with imaging studies on a larger sample size, which is known as genetics-imaging, would be a suitable approach for tracing this process.